Discount pricing strategies for smart phone using system dynamics modelling - Mat Zaib, Nurul Afiqah (Penerbit UTM Press, 2016)
Nowadays, retailers of highly demanded products such as fashion goods and high technology electronic devices (smart phone) are aggressively competing with one another in order to increase revenue and to maintain their position in the market place. Rapid introduction of new smart phone into the market has resulted in shorter product life cycle and intensified competition, which force retailers to enhance their strategic management and creates competitive advantages. The challenge is in designing a suitable pricing strategy and discount offerings. Thus, the aim of this research is to develop a dynamic model to understand the relations between factors influencing the discount-pricing decision, to analyze performance of the discount-pricing strategy and to present an insight on the effects of the strategy implemented. Hence, to help achieve all the purposes, system dynamics approach is chosen to model the discount-pricing strategy for new smart phone. System dynamics modelling simulates the behavior of complex systems over time. Data used in the research is collected from literature review and email interview. The email interview focuses on the information of discount-pricing strategy normally used by retailers. The simulation results show that the value of cumulative sales within introduction phase is the highest as compared to other phases. Based on the survey, it is proposed that suitable discount level to be offered for new smart phone ranges from 10 to 30. Furthermore, the study suggests that retailers can start a discount promotion early of the month of new smart phone released and, in addition, the discount-pricing strategy model of new smart phone is also produced as one of contribution of this study.